DEVELOPING ISLAMIC-BASED READING MATERIALS FOR THE TENTH GRADERS OF MA NURUL HUDA KASMARAN OF BABAT TOMAN - SUSILAWATI SUSILAWATI; TAHRUN TAHRUN; RITA INDERAWATI (Sriwijaya University Learning and Education International Conference, 2016)
The purpose of this study was to find out the developing Islamic-based reading materials text were valid, practical, and potential effect of the Islamic-based reading materials text. Development research consisting of analysis, design, evaluation and revision was used in developing the product. To collect the data, questionnaires and a test were used. The data were analyzed by using average score for the questionnaires and percentage for the test. In evaluation phase, formative evaluation consisting of self-evaluation, experts review, one-to-one, small group, and field test was also used. There were two Islamic experts reviewing the product, three students involved in one-to-one evaluation, nine students involved in small group evaluation, and 20 students of a real class involved in field test. The developed product was valid based on the result of the expert review phase in terms of its content. One was expert of content and another one was expert of instructional design. The result of experts judgment showed that the product was valid with average score was 89,2 categorized in good validity. The product was practical with average score in one-to-one evaluation was 84,3 and in small group phase was 86.6. The effectiveness of the product could be seen from the average score of students’ achievement in field test. The score was 92.8 meaning that score was higher than the criterion of minimal mastery (KKM) of English subject in MA Nurul Huda Kasmaran 75. Therefore, the product had potential effect categorized in good level.